Recruiting recent graduates to work at agricultural enterprises: Siberian region case study - Babenko, Andrey; Mukhin, Leonid (Applied Studies in Agribusiness and Commerce, 2017)
The authors present the results of the analysis of the employment of graduates of agricultural specialties in the Siberian Federal District of the Russian Federation. In the Siberian Federal District, more than 20 universities are engaged in the training of specialists in agriculture. The universities pay special attention to the employment of their graduates and often have their own programs of graduates’ employment.The article is devoted to discussing the reasons why the graduates consider the work in the rural area to be unattractive (low standards of living conditions compared with town, lack of quality education for children and possibilities for professional development, etc.) The necessity of realization of the state strategy intended to support graduates of agricultural specialties is grounded, including assigning the status of civil servants to social workers in rural areas and attracting successful entrepreneurs to the village and creating conditions for the development of the entrepreneurialenvironment.JEL Code: J21